A randomised controlled trial of student nurse performance of cardiopulmonary resuscitation in a simulated family-witnessed resuscitation scenario. (May 2017) - Kenny, Gerard; Bray, Isabelle; Pontin, David; Jefferies, Rachel; Albarran, John
Abstract: This randomized controlled trial, conducted in a UK University nursing department, compared student nurses' performance during a simulated cardiac arrest. Eighteen teams of four students were randomly assigned to one of three scenarios: 1) no family witness; 2) a "quiet" family witness; and 3) a family witness displaying overt anxiety and distress. Each group was assessed by observers for a range of performance outcomes (e.g. calling for help, timing to starting cardiopulmonary resuscitation), and simulation manikin data on the depth and timing of three cycles of compressions. Groups without a distressed family member present performed better in the early part of the basic life support algorithm. Approximately a third of compressions assessed were of appropriate pressure. Groups with a distressed family member present were more likely to perform compressions with low pressure. Groups with no family member present were more likely to perform compressions with too much pressure. Timing of compressions was better when there was no family member present. Family presence appears to have an effect on subjectively and objectively measured performance. Further study is required to see how these findings translate into the registered nurse population, and how experience and education modify the impact of family member presence. Highlights: Simulation enables student nurses to practice BLS skills in a safe environment. In this RCT, family presence was found to affect the performance of CPR by student nurses. Approximately a third of compressions performed were of appropriate pressure. Groups with no family member present were more likely to perform compressions with too much pressure. Timing of compressions was better when there was no family member present.